Gut Microbial and Metabolic Profiling Reveal the Lingering Effects of Infantile Iron Deficiency Unless Treated with Iron. Issue 8 (8th March 2021) - Mayneris‐Perxachs, Jordi; Amaral, Wellington; Lubach, Gabriele R.; Lyte, Mark; Phillips, Gregory J.; Posma, Joram M.; Coe, Christopher L.; Swann, Jonathan R.
Abstract : Scope: Iron deficiency (ID) compromises the health of infants worldwide. Although readily treated with iron, concerns remain about the persistence of some effects. Metabolic and gut microbial consequences of infantile ID were investigated in juvenile monkeys after natural recovery (pID) from iron deficiency or post‐treatment with iron dextran and B vitamins (pID+Fe). Methods and Results: Metabolomic profiling of urine and plasma is conducted with 1 H nuclear magnetic resonance (NMR) spectroscopy. Gut microbiota are characterized from rectal swabs by amplicon sequencing of the 16S rRNA gene. Urinary metabolic profiles of pID monkeys significantly differed from pID+Fe and continuously iron‐sufficient controls (IS) with higher maltose and lower amounts of microbial‐derived metabolites. Persistent differences in energy metabolism are apparent from the plasma metabolic phenotypes with greater reliance on anaerobic glycolysis in pID monkeys. Microbial profiling indicated higher abundances of Methanobrevibacter, Lachnobacterium, and Ruminococcus in pID monkeys and any history of ID resulted in a lower Prevotella abundance compared to the IS controls. Conclusions: Lingering metabolic and microbial effects are found after natural recovery from ID. These long‐term biochemical derangements are not present in the pID+Fe animals emphasizing the importance of the early detection and treatment of early‐life ID to ameliorate its chronic metabolic effects. Abstract : Iron deficiency anemia is a common nutritional and pediatric concern worldwide. In addition to the known effects on red blood cells, iron has diverse effects on oxidative metabolism and synthesis pathways. In this study, lingering metabolic and gut microbial disruptions are observed in juvenile monkeys that had naturally recoveried from infantile iron deficiency. These persistent metabolic effects are prevented with the rapid treatment of early‐life iron deficiency with iron dextran and B vitamins. These findings highlight the importance of identifying and treating infantile iron deficiency early in life.